8.4k views
0 votes
|-2y+6|=6 please show the steps involved!!!

2 Answers

4 votes

Answer:

Explanation:

Rearrange this Absolute Value Equation

Absolute value equalitiy entered

|-2y+6| = 6

STEP

2

Clear the Absolute Value Bars

Clear the absolute-value bars by splitting the equation into its two cases, one for the Positive case and the other for the Negative case.

The Absolute Value term is |-2y+6|

For the Negative case we'll use -(-2y+6)

For the Positive case we'll use (-2y+6)

STEP

3

Solve the Negative Case

-(-2y+6) = 6

Multiply

2y-6 = 6

Rearrange and Add up

2y = 12

Divide both sides by 2

y = 6

STEP

4

Solve the Positive Case

(-2y+6) = 6

Rearrange and Add up

-2y = 0

Divide both sides by 2

-y = 0

Multiply both sides by (-1)

y = 0

Which is the solution for the Positive Case

STEP

5

:

Wrap up the solution

y=6

y=0

Two solutions were found :

y=0

y=6

User Pieter Herroelen
by
5.7k points
6 votes

Answer:

y = 6 or y = 0

Explanation:

|-2y + 6| = 6

-2y + 6 = -6 -2y + 6 = 6

-2y = -12 -2y = 0

y = 6 y = 0

Best of Luck!

User Eduardo Pereira
by
6.2k points